Demanding Legal Reforms for Climate-Induced Groundwater Salinization in Jaffna Peninsula: A Legal Analysis - Thilakarathne, W.G.T.Y. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Nearly all of the Jaffna Peninsula is dependent on a shallow freshwater aquifer system that is particularly susceptible to stresses brought on by climate change. Salinization is accelerating throughout the region due to rising sea levels, protracted droughts, excessive groundwater extraction, and decreasing recharge rates, endangering public health, agriculture, long-term sustainability, and the security of drinking water. Though this has already marked its urgency, the lack of comprehensive legal framework to handle ground water extraction, monitoring, and climate resilience. As a result, the lacunae maintain without a fill. The handful of statutes that govern environmental law in the country, including The National Environmental Act, Coast Conservation Act, and Disaster Management Act provides only fragmented and indirect protection and it leads to significant gaps regarding aquifer rights, control of private wells, and limits on intensive pumping. Employing the qualitative method of research, and comparative legal analysis, the researcher critically examines legal vacuum surrounding groundwater governance in the Jaffna Peninsula and evaluates the extent to which climate change exacerbates existing vulnerabilities. Through comparative analysis of the regional models such as India and Bangladesh, the study argues the necessity of establishing robust legal framework through Groundwater Protection and Climate Resilience Act in Sri Lanka. Thus, the paper suggests for a regulatory architecture centred on licensing, monitoring, community participation, and climate-informed aquifer management. Through the discussion and the lessons taken from selected other jurisdictions, the researcher emphasizes that in addition to ensuring environmental security, strengthening groundwater laws is crucial for safeguarding Northern Sri Lankan communities’ constitutional rights to life, health, and a clean environment.
Keywords: Water salinization; Ground water; Jaffna peninsula; Climate resilience